Formative assessment in learning the right - Monge Núñez, Gonzalo (2015)
The accreditation marks a turning point in the history of the Faculty of Law. It is not the fact in itself, but because a commitment is made to upgrade the teaching and improve learning. This involves reviewing the content of the curriculum and promotes new ways of teaching. For this purpose the formative evaluation of the process is a proposal in accordance with the times and the challenges which faces the Faculty of Law, in this new stage